Multiple Intelligence Menentukan Jurusan di SMA Menggunakan Teknik Multi-Attribute Decision Making - Moh. Ahsan; Purnomo Budi Santoso; Harry Soekotjo Dachlan (Fakultas Teknik, Universitas Brawijaya, 2015)
Decision Support System is an application that can assist students in determining the direction in senior high school (SMA) based on Multiple Intelligence tests using techniques MADM (Multiple-Attribute Decesion Making) by the method of Simple Additive Weighting (SAW) and Analytic Hierarchy Process (AHP). Multiple Intelligence is used to determine the intelligence possessed by the students based on test results. The input of this system is the student academic data, questionnaire specialization, psychologists and test data is Multiple Intelligence.The results of analysis system showed that the most influential factor in determining of the majors based on interest is the interest of students, academic grades, test psychologist and wishes of parents. The recommendations manual majors only based on the value of report cards, grades National Examination and Intelegent Quotient scores. Accuracy in the calculation of the value system based SAW method has an accuracy of 80% according to the student's choice. While the decision by the AHP method has an accuracy of 30% in accordance with the student's choice.Index Terms —Multiple Intelligence, Multi-Attribute Decision Making, Simple Additive Weighting Method and Analytic Hierarchy Process.